Letter from the Editor - Sekhri, Rajiv (Satura, 2022)
Welcome to the fourth edition of Satura, the student journal of the English Department at Westfälische Wilhelms Universität in Münster. The theme of issue 4 – Crucibles of Transition – asked students from around the world to explore how identity, war, gender, disease, climate change, sexuality, class, nationality, language and other forms of difference help us connect and disconnect. We wanted to bring together student voices to reflect and give us a sense of the world as they see it.